2014
DOI: 10.3390/foods3030527
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acetic Acid against Listeria monocytogenes Attached to Poultry Skin during Refrigerated Storage

Abstract: This work evaluates the effect of acetic acid dipping on the growth of L. monocytogenes on poultry legs stored at 4 °C for eight days. Fresh inoculated chicken legs were dipped into either a 1% or 2% acetic acid solution (v/v) or distilled water (control). Changes in mesophiles, psychrotrophs, Enterobacteriaceae counts and sensorial characteristics (odor, color, texture and overall appearance) were also evaluated. The shelf life of the samples washed with acetic acid was extended by at least two days over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…However, in their study, the 0.4% dry vinegar treatment was not effective at controlling Listeria growth. These results are also in agreement with results reported by McDonnell et al (2013) and Gonzalez-Fandos and Herrera (2014). These researchers reported that the antimicrobial effect of vinegar and other natural or cleanlabel antimicrobials is impacted by the concentration that is included in the product.…”
Section: Microbial Analysissupporting
confidence: 92%
“…However, in their study, the 0.4% dry vinegar treatment was not effective at controlling Listeria growth. These results are also in agreement with results reported by McDonnell et al (2013) and Gonzalez-Fandos and Herrera (2014). These researchers reported that the antimicrobial effect of vinegar and other natural or cleanlabel antimicrobials is impacted by the concentration that is included in the product.…”
Section: Microbial Analysissupporting
confidence: 92%
“…Most commercial products use the combination of acids and/or salts to accomplish their synergistic effects. However, it is important to consider the specific inhibitory effects of each acid before supplementation (Gonzalez‐Fandos & Herrera, ; Sansawat, Lee, Singh, Ha, & Kang, ) (Figure ).…”
Section: Role Of Acidifiers In Nutritionmentioning
confidence: 99%
“…One possible intervention strategy could be the treatment with organic acids (González‐Fandos and Dominguez , ; González‐Fandos et al . ; Simón et al ., ; González‐Fandos and Herrera , ; Carpenter et al . ).…”
Section: Introductionmentioning
confidence: 99%